Arctic Environmental Test of Automatic Crew Served Weapons - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The objective of the procedure is to provide a means of evaluating the performance of automatic crew served weapons under arctic winter environmental conditions.